Markers of occupational stress (MOS): Archaeological case studies - Hincak, Zdravka (Array, 2009)
Markers of occupational stress (MOS) represent anatomical irregularities on human skeleton, either as a result of hard tissue modification or pathological condition. It is always connected with numerous activities related to work. Four skeletons from different archaeological periods were analysed, from Neolithic (Early Stone Age) to Late Roman Period of Croatia and Slovenia. Specific bone and teeth modifications were found on several anatomical elements of each persons skeleton. It was of great importance to comprised in analysis the total preserved skeleton elements and not exclusively those with marked irregularities. The results of the analysis represents development of specific MOS patterns on skeletons of swimmer/diver (Neolithic period), horseback rider (Late Roman Period), skeleton of a person whose everyday activities includes unique postures of sitting and kneeling (Vučedol culture). The fourth skeleton provide us a data how the pathological condition on foot bones drastically developed and changed the other anatomical elements. Analysed MOS patterns offer a more precise identification of an individual and has broad application in the field of forensic anthropology. However, analysis of MOS patterns on archaeological human material is giving deeper inside in paleodemographic studies of populations, not just a „ life story“ of certain individual.